2021
DOI: 10.1111/mcn.13197
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of geographic variation among correlates of child undernutrition in India

Abstract: Prior research has identified a number of risk factors ranging from inadequate household sanitation to maternal characteristics as important determinants of child malnutrition and health in India. What is less known is the extent to which these individual-level risk factors are geographically distributed. Assessing the geographic distribution, especially at multiple levels, matters as it can inform where, and at what level, interventions should be targeted. The three levels of significance in the Indian contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…First, the relative importance of lower levels has been shown in previous studies in the context of child malnutrition. For example, much of the geographic variation in household poverty and the risk factors for child malnutrition is attributable to cluster and between-cluster variation (19)(20)(21). Another study found that most of the geographic variation in child anthropometry and hemoglobin measures was attributable to within-cluster, or household, differences, further underscoring the importance of lower geographic levels (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the relative importance of lower levels has been shown in previous studies in the context of child malnutrition. For example, much of the geographic variation in household poverty and the risk factors for child malnutrition is attributable to cluster and between-cluster variation (19)(20)(21). Another study found that most of the geographic variation in child anthropometry and hemoglobin measures was attributable to within-cluster, or household, differences, further underscoring the importance of lower geographic levels (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future research should examine the district and cluster level factors that might explain this small area variation in dietary diversity. Doing so could help lower within district inequality and improve overall nutrition outcomes, especially considering that India's Integrated Child Development Services (ICDS) already implements interventions at the village level ( 19 ). Our results can help state-level policy makers identify the specific determinants of dietary diversity within district and between villages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and prevalence of disease in certain populations, climates, environments, are all related to the geographical location. Geographic variations in undernutrition and BMI have been documented in children, adolescents, adults, and older residents in nursing homes (24)(25)(26)(27).…”
Section: Geographic Variations Of Low Bmimentioning
confidence: 99%
“…However, regional variations in malnutrition indicators remain a matter of concern, with some states performing significantly poorer than others ( India State-Level Disease Burden Initiative CGF Collaborators, 2019 ). Several studies have used multilevel approaches to assess the contribution of various geographical factors to variations in child malnutrition indicators in India and other developing countries ( Amegbor et al, 2020 ; Jain, Rodgers, Li, Kim, & Subramanian, 2021 ; Marini & Gragnolati, 2006 ; Smith & Shively, 2019 ). However, most of these studies did not consider the confounding effects of team-level performance on regional data quality.…”
Section: Introductionmentioning
confidence: 99%